Urea import by China and its implications for India - Sanjay Kumar (1999)
India and China have been major importers of urea in the recent times. China has embarked on attaining self-sufficiency in urea production. They consider this strategy crucial for attaining self-sufficiency in grain production. This is also part of their modernisation plan of the domestic fertiliser industry. This article (which is a sequel to another special article published in January 9, 1999 issue of the EPW entitled `New Fertiliser Policy: a practical approach) studies the Chinese policy and its implications for the policy of India on expanding the domestic production capacity. The paper calls for a rational approach to the issue of domestic production after taking a considered view on the various aspects related to it. - Reproduced
Keywords: Fertilizers